2006
DOI: 10.1080/02698590600640992
|View full text |Cite
|
Sign up to set email alerts
|

How Science Is Applied in Technology

Abstract: Distinctive to basic sciences, scientific research in advanced technologies aims to explain, predict, and (mathematically) describe, not phenomena in nature, but phenomena in technological artefacts, thereby producing knowledge that is utilized in technological design. This article first explains why the covering-law view of applying science is inadequate for characterizing this research practice. Instead, the covering-law approach and causal explanation are integrated in this practice. Ludwig Prandtl's approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…This focus on mathematically oriented disciplines has led to some important insights, but it has also led to some distortions. Specifically, accounts of the applications of science have centered on the role of approximations and idealizations in the procrustean effort to find mathematical descriptions of (or laws governing) systems of practical interest (see Boon 2006 andCartwright 1976 for examples). As a partial remedy for this, I have attempted to provide a general account of how the theory of organic chemistry underwrites the process of designing and implementing a synthetic plan.…”
Section: Introductionmentioning
confidence: 99%
“…This focus on mathematically oriented disciplines has led to some important insights, but it has also led to some distortions. Specifically, accounts of the applications of science have centered on the role of approximations and idealizations in the procrustean effort to find mathematical descriptions of (or laws governing) systems of practical interest (see Boon 2006 andCartwright 1976 for examples). As a partial remedy for this, I have attempted to provide a general account of how the theory of organic chemistry underwrites the process of designing and implementing a synthetic plan.…”
Section: Introductionmentioning
confidence: 99%
“…Is this ok? AQ5 " Ackermann , 1985;Boon 2006;Cartwright 1989Cartwright , 1999Chang 2004;Dupré 1993;Orzack and Sober 1993;Woodward 1992;Galison 1987;Galison and Stump 1996;Mayo 1996;Giere 1988;Ladyman 2002" are not cited in the text part. Please provide citations.…”
Section: Chapter 12mentioning
confidence: 99%
“…On the other hand, scientific models try to describe the physical situation as accurately as possible. When scientists found that there are inadequacies in their scientific models, they may try to improve them by incorporating more domain-specific technical knowledge to make their scientific models more realistic (Boon, 2006), or they may develop a new theory with a new set of related scientific models as an alternative to the existing ones.…”
Section: Related Workmentioning
confidence: 99%
“…The focus of many engineering research works is to find better solutions to a technical problem (Boon, 2006). These solutions may involve some mathematical techniques or experimental know-how.…”
mentioning
confidence: 99%
See 1 more Smart Citation